Measuring adductor muscle activity during passing and 90°-cutting to investigate their role in the development of groin injuries - Dupré, T.; Tryba, J.; Potthast, W. (ISBS Proceedings Archive (Michigan), 2020)
Cutting manoeuvres and inside passing are thought to increase the risk of groin injuries, but research provides only little information in this regard. The purpose of the study was to compare the muscle activation of gracilis and adductor longus during a 90°-cutting manoeuvre and inside passing. Thirteen male soccer players performed the two movements. Muscle activity was measured with surface electromyography. Cutting showed higher maximum activations compared to passing in all investigated muscles. Activation during passing was high when considering that it is a submaximal effort with high amounts of repetition during match and training. Cutting showed the highest adductor activity during movement phases requiring eccentric contraction. Therefore, both movements are likely to put high loads on the adductor muscles and thereby increase the risk of groin injuries.